2023
DOI: 10.1002/biot.202300229
|View full text |Cite
|
Sign up to set email alerts
|

Improving statins production: From non‐genetic strategies to genetic strategies

Abstract: Statins are lipid‐lowering drugs that selectively inhibit 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase, effectively reducing cholesterol synthesis. With improved nutritional conditions, the demand for statins is increasing in the global market. The use of microbial cell factories for statin biosynthesis has become advantageous due to the rapid advancements in biotechnology. These approaches offer simple operation and easy separation of products. This review provides an overview the strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…In recent years, research on Acremonium chrysogenum has shifted from traditional mutagenesis breeding to rational engineering based on synthetic biology, similar to other industrial microorganisms, [ 1 ] for cephalosporin C (CPC) production. Although some gene editing studies have been reported in A. chrysogenum , [ 2 ] the improvement in CPC titer by metabolic engineering is generally low.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on Acremonium chrysogenum has shifted from traditional mutagenesis breeding to rational engineering based on synthetic biology, similar to other industrial microorganisms, [ 1 ] for cephalosporin C (CPC) production. Although some gene editing studies have been reported in A. chrysogenum , [ 2 ] the improvement in CPC titer by metabolic engineering is generally low.…”
Section: Introductionmentioning
confidence: 99%